The intergenerational transmission of education. Evidence from the World War II cohorts in Europe - Enkelejda Havari; Franco Peracchi (Publications Office of the European Union, 2019)
Abstract: The negativ e long-term effects of World War II on those directly exposed to it are well documented, but there is no evidence whether these effects extended to subsequent generations. Our paper aims to fill this gap by analyzing the intergenerational effects of World War II in terms of educational attainments. We focus on parent-children dyads in which parents were born between 1926 and 1949, and show two things. First, parents who suffered the war, that is, were exposed to major war events or personally experienced war-related hardship, ended up with less schooling than parents with similar characteristics who did not. Second, the children of parents who suffered the war have lower educational attainments than the children of parents with similar characteristics who did not suffer the war. Our reduced form results allow us to derive instrumental variables estimates of the coefficient of intergeneration transmission of education, which show that the effect of parental education is stronger for mothers than for fathers. They also show that the mother's education matters more for daughters than for sons.
Keywords: I0; J24; J3; 330; Education; Intergenerational effects; War; Conflict; Hunger; Hardship; World War II; Europe: SHARE